Chapter Russia, Armenia, Europa nella visione di Andrej Bitov - Marchesini, Irina (Biblioteca di Studi Slavistici, 2019)
The article explores the cultural and linguistic interrelationship of Russia, Armenia and Europe through the lens of quotation and intertextuality in Andrei Bitov's Armenian Lessons (first edition 1969). This text is the ideal site for demonstrating the importance of quotation in the author's prose. We address two different aspects of this question, first Bitov's literary and cultural intertextual references; second, his quotations from everyday language. In both cases, the "language of the Other" seeps into the text, forming bridges that connect apparently distant cultures.